Evaluating reading preparatory class for the regional assessment in junior high school with CIPP Model - Allan Suarman; Didik Rinan Sumekto; Dominique Savio Nsengiyumva (Universitas Sarjanawiyata Tamansiswa, 2025)
This research is proposed to evaluate an afterschool program called Reading Preparatory Class (RPC) for the ninth graders in order to prepare them to face the regional assessment called ASPD (Asesmen Standardisasi Pendidikan Daerah) with CIPP model. This research uses a descriptive qualitative approach and employs interview, questionnaires and content analysis in data collection. The findings show that there are strengths and shortcomings in the context, input, process and product of the program. In the context, the program has met needs of the students and been part of curriculum development. In the input, the materials have reflected the blueprint of the assessment although the source, author, and time of writing or publishing in the texts should be inserted. In the process, some students were still confused in word derivation, grammar and connectors for micro skills and identifying main idea, literal and implied meaning for macro skills, still needed to practice skimming to get main idea and scanning to know inferred sentences. In the product, the students’ achievement was still low in average but higher than almost schools in the regency. It is concluded that CIPP model is a thorough approach to assess the program from the planning to the result.